Relationship between stage of chronic liver disease and thrombocyte functions - Muhsin KAYA,; Aylin YAMAN,; Şule Mine YAMAN,; Nazmiye KURŞUN,; Selim KARAYALÇIN, (Turkish Journal of Gastroenterology, 2019)
-